Mobile Computing Technology and Applications - Khatib, Mutamed; Salman, Nael (IntechOpen, 2018)
Nowadays, mobile communication services are penetrating into our society at an explosive growth rate. Applications in mobile devices offer limitations, restriction, and guidelines on how mobile software can be used in order to simplify the mobile usage. As smart phones and tablets are becoming the daily computing device of choice for young ages, it is expected that mobile applications and services should be as flexible, high quality, and secure as the desktop systems. In this book, latest trends in mobile computing will be discussed. In the first section, cloud computing topics will be discussed widely into four chapters to give information to the reader about topics such as challenges, services, edge computing, and distributed clouds needed to integrate this promising issue into the next generation.